Discovery Learning Model with Interactive Flipbook Media on Critical Thinking Ability and Desire to Know - Ida Nur Hasanah; Rusnilawati Rusnilawati (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2023)
This investigation was motivated by the low levels of critical thinking and curiosity among elementary school pupils. This study seeks to describe the disparities in fourth-grade students' comprehension of square and rectangular shapes before and after using the Discovery Learning model with Flipbook-interactive media. The method of investigation employed is quantitative research. This study employs a pretest and posttest design with a control group. This study employed assessments, questionnaires, observation, and documentation for data collection. Statistical analysis comprising normality tests, homogeneity tests, paired sample t-tests, independent sample t-tests, and ANOVA tests was used to perform data analysis techniques. Based on the results of the study, which showed that students' critical thinking skills obtained a sig. of 0.000 > 0.05, Ha is accepted and Ho is rejected, so that students' critical thinking after using the Discovery Learning model with Flipbook-interactive media is better than before using it. In the attitude of curiosity of students, the value of sig. is 0.000 > 0.05, then Ha is accepted and Ho is rejected, so that After employing the Discovery Learning paradigm with Flipbook-interactive media, students have a more inquisitive disposition than before. Meanwhile, critical thinking skills and an attitude of curiosity obtained F 2.916 with a sig. equal to 0.000 > 0.05, then Ha is accepted and Ho is rejected, so that critical thinking skills and curiosity after using the Discovery Learning model with Flipbook-interactive media are better than the cooperative model with visual aids.